Serogroup Distribution of Shigella in Tehran - R Ranjbar; MM Soltan Dallal; MR Pourshafie; MM Aslani; R Majdzadeh (Tehran University of Medical Sciences, 2004)
In recent years, the importance of Shigella as an enteric pathogen with global impact has been increasingly recognized. In this study, serogroup distribution of Shigella isolated from clinically diagnosed cases of gastroenteritis and acute diarrhea in Tehran, capital of Iran was investigated between December 2002 and November 2003. Fecal specimens and rectal swabs were cultured for Shigella spp. using standard microbiological techniques. The isolates of Shigella were identified by biochemical assay and serological testing. From a total of 302 Shigella isolates, 178, 110, 10 and 4 strains were identified as S.sonnei (58.9%; 95% CI: 53.2-64.5), S. flexneri (36.4%; 95% CI: 31.0-42.2), S.boydii (3.3%), and S. dysenteriae (1.3%), respectively. The peak of infection occurred during summer. Overall, 167 patients (55.3%) were males and 135 (44.7%) were females